A Dedicated Satellite Trauma Orthopaedic Program Operating Room Safely Increases Capacity. (16th May 2018) - Waters, Peter M.; Yang, Brian W.; White, Doreen; Barth, Ellen; Chiang, Vincent; Mizrahi-Arnaud, Arielle; Sparks, William
Abstract : Background: Providing high-value care for urgent orthopaedic trauma patients requires effective and timely treatment. Herein, we describe the implementation of an innovative program utilizing the operating room (OR) capacity of a satellite campus to decrease stress on a pediatric tertiary care center without jeopardizing patient safety. Methods: In addition to the daily emergency surgical room on the main campus, a dedicated orthopaedic trauma surgery OR was established in a satellite hospital location for 3 days per week in the summer and for 2 days per week for the rest of the year. Nonemergency, non-multitrauma operative fracture cases presenting to our tertiary care facility emergency department or orthopaedic clinic were considered for satellite referral. Eligible patients required clearance for transfer via orthopaedic, emergency department, and anesthesia checklists. An opt-out policy was established for provider judgment or patient family concern to overrule transfer decisions. Selected patients were discharged home with satellite OR scheduling or approved for same-day satellite location admission. Short elective cases were performed when openings existed in the schedule. Results: From June 1, 2016, through June 30, 2017, 480 cases (372 trauma, 108 elective) were completed in our satellite OR. The most common trauma cases that were treated in the satellite OR were type-II supracondylar humeral fractures (n = 76). Summer months averaged 41.75 trauma cases and 11.25 elective cases per month, with 3.15 trauma cases and 0.85 elective cases per day. Nonsummer months averaged 22.78 trauma cases and 7.00 elective cases per month, with 2.93 trauma and 0.90 elective cases per day. Of the 17 postoperative issues, the greatest number (n = 7 [41%]) involved symptomatic hardware. The remaining complications were not surgeon or geographic-site-specific. There were no intraoperative complications, compartment syndrome episodes, or patients who required transfer back to our tertiary care facility for unexpected or serious medical issues. Conclusions: With the proper screening protocols in place for appropriate patient selection, the use of a dedicated satellite orthopaedic trauma OR can increase capacity without compromising patient safety.